2007
DOI: 10.1097/mrr.0b013e3280146f57
|View full text |Cite
|
Sign up to set email alerts
|

Complex regional pain syndrome in stroke patients

Abstract: The objective of this study was to investigate the incidence, and the factors influencing the development, of complex regional pain syndrome-I in the upper extremity in hemiplegic patients within the first 28 weeks following a stroke. We followed up 82 stroke patients. All patients were evaluated at weeks 2, 6, 14 and 28 after suffering a stroke. Outcomes were assessed using passive range of motion of shoulder, presence of subluxation, Ashworth score, Motricity index arm score, Brunnstrom stages and depression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 9 publications
0
62
0
1
Order By: Relevance
“…The reported incidence of CRPS after stroke is variable, with estimates between 2 and 49% [90,91]. This variation is at least in part due to the lack of consensus on diagnostic criteria in previous studies.…”
Section: Common Post-stroke Pain Subtypesmentioning
confidence: 92%
“…The reported incidence of CRPS after stroke is variable, with estimates between 2 and 49% [90,91]. This variation is at least in part due to the lack of consensus on diagnostic criteria in previous studies.…”
Section: Common Post-stroke Pain Subtypesmentioning
confidence: 92%
“…With regards to depression, higher [17,18], comparable [19,20], and lower [21,22] levels of depression have been found in persons with CRPS when compared to other groups. In a similar manner, findings on anxiety and CRPS diverge, with reports of higher [18], comparable [19], and lower [23] anxiety levels in persons with CRPS in comparison to other groups.…”
Section: Introductionmentioning
confidence: 94%
“…[75][76][77][78][79] One recent prospective study recruited 82 patients with stroke and reported a positive correlation between subluxation and RSD. 76 Subluxation was assessed by plain radiographs using a five-point scale and a clinical diagnosis of RSD was made. Of the 46 patients with subluxation, 27 had RSD, while of 36 patients without subluxation, only 13 had RSD.…”
Section: Reflex Sympathetic Dystrophymentioning
confidence: 97%